2021
DOI: 10.1186/s13223-021-00583-w
|View full text |Cite
|
Sign up to set email alerts
|

Canadian food ladders for dietary advancement in children with IgE-mediated allergy to milk and/or egg

Abstract: Food ladders are clinical tools already widely used in Europe for food reintroduction in milk- and egg-allergic children. Previously developed milk and egg ladders have limited applicability to Canadian children due to dietary differences and product availability. Herein we propose a Canadian version of cow’s milk and egg food ladders and discuss the potential role that food ladders may have in the care of children with IgE-mediated allergies to cow’s milk and/or egg, as either a method of accelerating the acq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 22 publications
0
28
0
Order By: Relevance
“…Hereby, our step-wise introduction was based on the difference in thermal processing and heat-induced modifications of egg allergens in those preparations, as observed by SDS-PAGE and ELISA. Second, we introduce pancakes and waffles along with omelet, while others introduce these preparations earlier based on the “wheat matrix effect” and lower amount of egg per consumption ( 9 11 , 29 , 30 ). Although we also observed this “wheat matrix effect,” we chose to introduce hard-boiled egg in step two due to its low ovalbumin level and longer heating time and decided that solely relying on heating duration (which was ~3' for pancakes, waffles, and omelet) simplified the instructions for parents.…”
Section: Discussionmentioning
confidence: 99%
“…Hereby, our step-wise introduction was based on the difference in thermal processing and heat-induced modifications of egg allergens in those preparations, as observed by SDS-PAGE and ELISA. Second, we introduce pancakes and waffles along with omelet, while others introduce these preparations earlier based on the “wheat matrix effect” and lower amount of egg per consumption ( 9 11 , 29 , 30 ). Although we also observed this “wheat matrix effect,” we chose to introduce hard-boiled egg in step two due to its low ovalbumin level and longer heating time and decided that solely relying on heating duration (which was ~3' for pancakes, waffles, and omelet) simplified the instructions for parents.…”
Section: Discussionmentioning
confidence: 99%
“…3,43 Some study findings have suggested that these ladder approaches may function as a form of oral immunotherapy (OIT) in some patients. 18…”
Section: B Enefits and Con Cern S Of Us Ing Food Allerg En L Adder Smentioning
confidence: 99%
“…There is also the possibility that intake of foods with baked milk and egg content may accelerate the development of tolerance to uncooked milk and egg 3,43 . Some study findings have suggested that these ladder approaches may function as a form of oral immunotherapy (OIT) in some patients 18 …”
Section: Benefits and Concerns Of Using Food Allergen Laddersmentioning
confidence: 99%
See 2 more Smart Citations